Acute Radiation Syndrome and the Microbiome: Impact and Review - Hollingsworth, Brynn A.; Cassatt, David R.; DiCarlo, Andrea L.; Rios, Carmen I.; Satyamitra, Merriline M.; Winters, Thomas A.; Taliaferro, Lanyn P. (Frontiers in Pharmacology, 2021)
Study of the human microbiota has been a centuries-long endeavor, but since the inception of the National Institutes of Health (NIH) Human Microbiome Project in 2007, research has greatly expanded, including the space involving radiation injury. As acute radiation syndrome (ARS) is multisystemic, the microbiome niches across all areas of the body may be affected. This review highlights advances in radiation research examining the effect of irradiation on the microbiome, and its potential use as a target for medical countermeasures or biodosimetry approaches, or as a medical countermeasure itself. The authors also address animal model considerations for designing studies, and the potential to use the microbiome as a biomarker to assess radiation exposure and predict outcome. Recent research has shown that the microbiome holds enormous potential for mitigation of radiation injury, in the context of both radiotherapy and radiological/nuclear public health emergencies. Gaps still exist, but the field is moving forward with much promise.